Pemodelan Tiga Dimensi Struktur Bawah Permukaan Daerah Manifestasi Panas Bumi Menggunakan Data Gravitasi Satelit GGMplus - Muhammad Rofiqul A'la; Atika Windra Sari; Dian Arif Rachman; Elvinda Bendra Agustina; Yusril Ihza Tachriri; Rezqi Alfiandi; Rusliyanto Akbar (Jurnal Penelitian Teknologi Informasi dan Sains, 2026)
Gravity measurements in the Dieng geothermal area at regional and wide scales are still limited. GGMplus data provides large-scale gravity information that can be used for subsurface mapping more efficiently and at lower cost while maintaining optimal results. The GGMplus gravity acceleration data is processed into complete Bouguer anomalies, then separated using upward continuation to obtain regional and local anomalies. Both anomalies are further analyzed using the first horizontal derivative (FHD) and second horizontal derivative (SHD). The results are then used for 3D modeling using Grablox and Bloxer software. The Bouguer anomaly distribution ranges from approximately ‒70 to ‒230 mGal, with high anomalies located in the northeast of the study area, corresponding to geothermal manifestations in Dieng. FHD analysis indicates a regional anomaly source located 6.8 km northeast, interpreted as a magmatic zone. Local anomalies reveal an intrusion body about 2 km in size at a distance of 4 km in Mount Prau, interpreted as a heat source. The 3D model shows high-density values of 2.87 g/cm³ for regional anomalies and 2.8–2.9 g/cm³ for local anomalies, associated with ancient volcanic rocks and diorite intrusions acting as a heat source in the Sikidang–Merdada geothermal system.